Dysregulated fibroblast growth factor (FGF) signaling in neurological and psychiatric disorders - Turner, Cortney A. (Semin Cell Dev Biol, 2015)
The role of the fibroblast growth factor (FGF) system in brain-related disorders has received considerable attention in recent years. To understand the role of this system in neurological and psychiatric disorders, it is important to identify the specific members of the FGF family that are implicated, their location and the various mechanisms they can be modulated. Each disorder appears to impact specific molecular players in unique anatomical locations, and all of these could conceivably become targets for treatment. In the last several years, the issue of how to target this system directly has become an area of increasing interest. To date, the most promising therapeutics are small molecule inhibitors and antibodies that modulate FGF receptor (FGFR) function. Beyond attempting to modify the primary players affected by a given brain disorder, it may prove useful to target molecules, such as membrane-bound or extracellular proteins that interact with FGF ligands or FGFRs to modulate signaling.